Galerij William Wauters. (Oosteeklo : Galerie William Wauters, 1982)
Vlerick, Pierre ; Declerck, Antoon ; Goeters, Romain ; spilliaert, Pol ; De Kramer, Enk ; Dierickc, Karel ; Roobjee ; van Gysegem, Paul ; Vandenberghe, Philippe ; Vandendorpe, Willy ; Burssens, Jan ; Mendelson, Marc ; Raveel, Roger
Galerie William Wauters, Oosteeklo, Kalender 1981-1982
Nederlands
boek